Associations of Gastrointestinal Tract Tumor Necrosis Factor Receptor-Associated Factor 6 Expression with Clinical Features and Prognosis of Eosinophilic Gastroenteritis - Bai, Yaya; Tang, Yuming; Zhu, Ying; Yuan, Fei; Xu, Haimin; Yao, Weiyan (Turkish Journal of Gastroenterology, 2023)
Background: Few studies have been conducted to explore the expression of tumor necrosis factor receptor-associated factor 6 in eosinophilic gastroenteritis patients. Therefore, the expression profile of tumor necrosis factor receptor-associated factor 6 in the gastrointestinal tract of eosinophilic gastroenteritis patients and its associations with clinical features were explored in this study. Methods: Thirty-four eosinophilic gastroenteritis patients who presented in Ruijin Hospital from December 2012 to May 2019 and had accepted gastrointestinal endoscopic examinations were recruited. Medical records and endoscopic biopsies were collected, and the prognosis was followed up by telephone. Healthy persons were selected as the control group. Hematoxylin and eosin and immunohistochemical staining were performed in both eosinophilic gastroenteritis patients and healthy persons. The final results were analyzed by skilled pathologists, and mean optical density values of tumor necrosis factor receptor-associated factor 6 were calculated by Image J software. Final results were analyzed by Statistical Package for the Social Sciences software 22.0. Results: Thirty-four patients (mean age: 25.56 ± 21.14 years, 61.76% males) were recruited for this study. There was no significant difference in tumor necrosis factor receptor-associated factor 6 mean optical density values of gastric tissues in eosinophilic gastroenteritis patients and healthy people (0.22 ± 0.16 vs. 0.14 ± 0.05, P > .05). Eosinophilic gastroenteritis patients had a significantly lower level of intestinal tumor necrosis factor receptor-associated factor 6 mean optical density values than that of healthy people (0.16 ± 0.05 vs. 0.23 ± 0.06, P < .05). Intestinal tumor necrosis factor receptor-associated factor 6 mean optical density values negatively linearly correlated with serum interleukin-10 level (r = −0.618, P = .043 < .05). There were no differences between eosinophilic gastroenteritis patients with or without relapse regarding the expression level of intestinal tumor necrosis factor receptor-associated factor 6 (P = .227 > .05). Conclusion: Patients with eosinophilic gastroenteritis might have a deficiency of intestinal tumor necrosis factor receptor-associated factor 6 compared to healthy controls.